2021
DOI: 10.1021/acs.chemrev.0c01304
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Polymer Networks

Abstract: Polymer networks are complex systems consisting of molecular components. Whereas the properties of the individual components are typically well understood by most chemists, translating that chemical insight into polymer networks themselves is limited by the statistical and poorly defined nature of network structures. As a result, it is challenging, if not currently impossible, to extrapolate from the molecular behavior of components to the full range of performance and properties of the entire polymer network.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
199
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(201 citation statements)
references
References 643 publications
2
199
0
Order By: Relevance
“…We begin with an investigation of the cross-link coordination per monomer and the network fractal dimension. These structural properties have been analysed in the context of many biological networks[50, 51], and identified as useful in the characterisation of polymeric networks[52]. We previously calculated these values in monomeric pseudo-colloidal networks[32] where both were shown to affect the pore size distribution and mechanical response of those networks.…”
Section: Figmentioning
confidence: 99%
“…We begin with an investigation of the cross-link coordination per monomer and the network fractal dimension. These structural properties have been analysed in the context of many biological networks[50, 51], and identified as useful in the characterisation of polymeric networks[52]. We previously calculated these values in monomeric pseudo-colloidal networks[32] where both were shown to affect the pore size distribution and mechanical response of those networks.…”
Section: Figmentioning
confidence: 99%
“…The macroscopic properties of rubbers required for industrial applications are strongly related to the complex structure of the three-dimensional network of crosslinks formed during vulcanization [17][18][19][20][21][22]. This structure is defined by the number and spatial distribution of crosslinks and by their functionality and chemical nature, as well as by the presence of defects (pendant chains, loops, and chain modifications) and entanglements.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, several strategies have been applied with the main focus on phase separation, [21–23] cross‐linking density, [4, 24–28] and the combination of permanent and transient bonds in order to hinder low temperature material deformation [29–33] . However, from a more general material design point of view, [34] a (theoretically) defect‐free vitrimer should show only elastic behaviour upon deformation [35] . Especially when considering that for most known vitrimer chemistries, it was experimentally demonstrated that viscous flow relies on the presence of reactive chain ends or side chains.…”
Section: Introductionmentioning
confidence: 99%